Analysis of Environmental and Economic Prospects of Stand-By Solar Powered Systems in Nigeria - A. Offiong; Nseobong I. Okpura (Mathematical and Software Engineering, 2016)
Photovoltaic power systems can be used as electrical power source for home to meet its daily energy requirement through direct conversion of solar irradiance into electricity. This paper presents environmental and economic analysis of two stand-by power supply options for a typical Nigerian household namely: diesel generator plant and solar powered systems. The analysis reveals that solar systems are more economically viable. The environmental benefits associated with substituting diesel powered stand-by plants with solar powered photovoltaic systems were also estimated. The amount of diesel saved was estimated and the reduction in air pollution calculated. With these two analyses, it is hoped that individual households in Nigeria, will be encouraged to go for solar stand-by systems while government will be encouraged to pursue further on energy-environmental friendly policy which will lead to the reduction in the production of air pollutants. This kind of policy is very essential, as the number of household installing stand-by power plants in Nigeria has been found to increase significantly over the past few years.